Optimalisasi Pemberdayaan Masyarakat Melalui Program Kuliah Kerja Mahasiswa:: Studi Kasus di Desa Ngebruk, Poncokusumo, Malang - Cielo, Esperanza (Maliki Interdisciplinary Journal, 2025)
The Student Work Study (KKM) is an implementation of the Tri Dharma of Higher Education, especially in community service. This research aims to evaluate the KKM program implemented in Ngebruk Village, Poncokusumo District, Malang Regency, with a focus on community empowerment through educational, social, and economic activities. The approach used is the Asset-Based Community Development (ABCD) method, with emphasis on the Discovery and Destiny stages. The results showed that the KKM program had a positive impact in various aspects. In the education sector, teaching activities at SDN 1 Ngebruk, TPQ Sabilut Taqwa, TPQ Qurrota A'yun, and Rumah Belajar succeeded in increasing students' learning motivation. In the social sector, activities such as community service, participation in posyandu activities, and involvement in weekly and monthly religious routines strengthen social interactions and residents' concern for the environment. Meanwhile, in the economic field, student participation in supporting local MSMEs, such as seed and vegetable MSMEs and tofu MSMEs, contributed to the development of local businesses. In conclusion, the implementation of the KKM in Ngebruk Village succeeded in making a real contribution in empowering the community, both in terms of education, social, and economy. This success was achieved through active collaboration between students, the community, and related parties, which is expected to create a long-term impact on village development.